2016
DOI: 10.1007/s13178-016-0238-9
|View full text |Cite
|
Sign up to set email alerts
|

The Gentle Neoliberalism of Modern Anti-bullying Texts: Surveillance, Intervention, and Bystanders in Contemporary Bullying Discourse

Abstract: The author argues for the concept of "gentle" neoliberalism to account for how discourse in anti-bullying texts has increasingly presented itself as gentle and kind, while simultaneously reinforcing systems of surveillance and control. Results, based on a grounded theory analysis of 22 antibullying books, reveal that the texts generally decoupled bullying from power relations based on sexuality, overlooking homophobia and heteronormativity and marginalizing the experiences of lesbian, gay, bisexual, and transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…A current meta-analysis (Kljakovic et al) conducted on predictors of bullying confirmed that conduct, social, peer and school problems predict bullying behaviors. In other surveys in Finland, guided by Sourander, these factors are corroborated as a risk factor for cyber bullying (10, 12, 17 and 39).…”
Section: Discussionmentioning
confidence: 73%
“…A current meta-analysis (Kljakovic et al) conducted on predictors of bullying confirmed that conduct, social, peer and school problems predict bullying behaviors. In other surveys in Finland, guided by Sourander, these factors are corroborated as a risk factor for cyber bullying (10, 12, 17 and 39).…”
Section: Discussionmentioning
confidence: 73%
“…Although some dismiss bullying and other forms of aggression as a normal part of the school experience, the association between these behaviors and suicides and school shootings, as well as a host of other negative effects, reveals the importance of addressing these interactions (Carney 2000;Ghandour et al 2004;Takizawa, Maughan, and Arseneault 2014). To do so, newer anti-bullying texts place an emphasis on reporting and intervention (Meyer 2016), yet within schools there is a continued reluctance on the part of students to report these behaviors to adults (Smith and Shu 2000;Garpelin 2004;Oliver and Candappa 2007). Further, adults sometimes downplay or ignore these interactions even when they are reported or directly observed (Garpelin 2004;Oliver and Candappa 2007;Thomson and Gunter 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although this historical change is usually contextualized as progress, scholarship has pointed to how these developments have primarily benefited LGBTQIA people with race and class privilege (Daum, 2015; Dwyer & Tomsen, 2016; Spade, 2015). That is, these changes are part of, and have contributed to, expanding hierarchies in LGBTQIA communities based on race, class, and gender (Hanhardt, 2013; Meyer, 2016; Russell, 2018). For instance, Hanhardt (2013) has shown that the separation of homosexuality from criminality occurred in part through mainstream gay-rights groups advancing representations of homosexuals as the victims of crime, rather than as criminals.…”
mentioning
confidence: 99%